Early Life Exposure to Fructose and Offspring Phenotype: Implications for Long Term Metabolic Homeostasis. (23rd April 2014) - Sloboda, Deborah M.; Li, Minglan; Patel, Rachna; Clayton, Zoe E.; Yap, Cassandra; Vickers, Mark H.
Abstract : The consumption of artificially sweetened processed foods, particularly high in fructose or high fructose corn syrup, has increased significantly in the past few decades. As such, interest into the long term outcomes of consuming high levels of fructose has increased significantly, particularly when the exposure is early in life. Epidemiological and experimental evidence has linked fructose consumption to the metabolic syndrome and associated comorbidities—implicating fructose as a potential factor in the obesity epidemic. Yet, despite the widespread consumption of fructose-containing foods and beverages and the rising incidence of maternal obesity, little attention has been paid to the possible adverse effects of maternal fructose consumption on the developing fetus and long term effects on offspring. In this paper we review studies investigating the effects of fructose intake on metabolic outcomes in both mother and offspring using human and experimental studies.